Exploring radiographers' experience with mobile X-ray of patients in their homes. Issue 1 (February 2022) - Bisgaard, M.; Andersen, P.A.B.; Jensen, A.T.; Sørensen, C.B.; Larsen, T.S.; Jensen, J.M.; Precht, H.
Abstract: Introduction: To offer citizens with frailty or dementia living in nursing homes or other institutions a less stressful and anxious X-ray examination, a Danish hospital offers to perform the examination in the citizen's residence. This has changed the working procedure for the radiographers performing the examination. The aim of this study was to explore if the radiographers self-perceived competencies have changed whilst working in the mobile X-ray unit and if so, how these competencies are utilised within the department-based medical imaging team. Method: This study had a qualitative design following a hermeneutic approach. Individual semi structured interviews included nine radiographers, four radiographers working in the mobile X-ray unit and five radiographers working exclusively in the medical imaging team. Results: Radiographers who worked in the mobile X-ray unit did acquire new competencies such as better communication and creative positioning skills. All nine participants recognised the advantage of sharing experiences and competencies with colleagues, and recommended a formal forum to do so. They sought opportunities for the use of the mobile X-ray unit to be more widespread within their own region, and within the profession. Conclusion: This study indicates that radiographers working with mobile X-ray unit gained new competencies in communication and positioning, but without spread of new knowledge to colleagues in the medical imaging team. Implication for practice: The use of home-based mobile X-ray is a new way to provide health care services and gain new competencies for the radiographers to focus on patient centred care.